Effect of Chronic Comorbidities on Follow-up Colonoscopy After Positive Colorectal Cancer Screening Results: A Population-Based Cohort Study - Bhatia, Dominika; Sutradhar, Rinku; Paszat, Lawrence F.; Rabeneck, Linda; Singh, Simron; Tinmouth, Jill; Lipscombe, Lorraine L. (The American journal of gastroenterology, 2022)
Fecal occult blood tests (FOBT) are colorectal cancer screening tests used to identify individuals requiring further investigation with colonoscopy. Delayed colonoscopy after positive FOBT (FOBT+) is associated with poorer cancer outcomes. We assessed the effect of comorbidity on colonoscopy receipt within 12 months after FOBT+. Population-based healthcare databases from Ontario, Canada, were linked to assemble a cohort of 50-74-year-olds with FOBT+ results between 2008 and 2017. The associations between comorbidities and colonoscopy receipt within 12 months after FOBT+ were examined using multivariable cause-specific hazard regression models. Of 168,701 individuals with FOBT+, 80.5% received colonoscopy within 12 months. In multivariable models, renal failure (hazard ratio, HR 0.71, 95% confidence interval, CI 0.62 to 0.82), heart failure (HR 0.77, CI 0.75 to 0.80), and serious mental illness (HR 0.88, CI 0.85 to 0.92) were associated with the lowest colonoscopy rates, compared to not having each condition. The number of medical conditions was inversely associated with colonoscopy uptake (≥4 vs. 0: HR 0.64, CI 0.58 to 0.69; 3 vs. 0: HR 0.75, CI 0.72 to 0.78; 2 vs. 0: HR 0.87, CI 0.85 to 0.89). Having both medical and mental illness was associated with lower colonoscopy uptake relative to no comorbidity (HR 0.88, CI 0.87 to 0.90). Persons with medical and mental health conditions had lower colonoscopy rates after FOBT+ than those without these conditions. Better strategies are needed to optimize colorectal cancer screening and follow-up in individuals with comorbidities.